The elucidation of the multimodal action of the investigational anti-Candida lipopeptide (AF4) lead from Bacillus subtilis - Ramesh, Swetha; Roy, Utpal; Roy, Subhashis (Frontiers in Molecular Biosciences, 2023)
Background: Candida species are the main etiological agents for candidiasis, and Candida albicans are the most common infectious species. Candida species' growing resistance to conventional therapies necessitates more research into novel antifungal agents. Antifungal peptides isolated from microorganisms have potential applications as novel therapeutics. AF4 a Bacillus-derived lipopeptide demonstrating broad-spectrum antifungal activity has been investigated for its ability to cause cell death in Candida species via membrane damage and oxidative stress.Methods: Using biophysical techniques, the secondary structure of the AF4 lipopeptide was identified. Scanning electron microscopy and confocal microscopy with fluorescent dyes were performed to visualise the effect of the lipopeptide. The membrane disruption and permeabilization were assessed using the 1,6-diphenyl hexatriene (DPH) fluorescence assay and flow cytometric (FC) assessment of propidium iodide uptake, respectively. The reactive oxygen species levels were estimated using the FC assessment. The induction of apoptosis and DNA damage were studied using Annexin V-FITC/PI and DAPI.Results: Bacillus-derived antifungal variant AF4 was found to have structural features typical of lipopeptides. Microscopy imaging revealed that AF4 damages the surface of treated cells and results in membrane permeabilization, facilitating the uptake of the fluorescent dyes. A loss of membrane integrity was observed in cells treated with AF4 due to a decrease in DPH fluorescence and a dose-dependent increase in PI uptake. Cell damage was also determined from the log reduction of viable cells treated with AF4. AF4 treatment also caused elevated ROS levels, induced phosphatidylserine externalisation, late-stage apoptosis, and alterations to nuclear morphology revealed by DAPI fluorescence.